2019
DOI: 10.1093/ofid/ofz155
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Rilpivirine-Based Regimens as Switch Therapy From Nevirapine-Based Regimens in Human Immunodeficiency Virus-Infected Patients With Virological Suppression: A Randomized Controlled Trial

Abstract: Background Nevirapine (NVP)-based antiretroviral therapy continues to be used in some human immunodeficiency virus (HIV)-infected patients. Rilpivirine (RPV) could be used as an alternative to NVP. We studied the efficacy of RPV-based regimens as switch therapy. Methods A randomized controlled noninferiority trial was conducted in HIV-infected patients who received NVP-based regimens and had undetectable plasma viral loads (VLs). Patients were randomized to a continuati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 19 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…Any disagreements were resolved by consensus. Eighteen articles met the inclusion criteria and were included in the systematic review [3][4][5][6][7][8][9][10][11][12][13][14]28,[32][33][34][35][36] (Table 1). Four of these articles were presented in tables and were not included in the quantitative metaanalyses of the efficacy and safety outcomes.…”
Section: Study Selection Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%
See 3 more Smart Citations
“…Any disagreements were resolved by consensus. Eighteen articles met the inclusion criteria and were included in the systematic review [3][4][5][6][7][8][9][10][11][12][13][14]28,[32][33][34][35][36] (Table 1). Four of these articles were presented in tables and were not included in the quantitative metaanalyses of the efficacy and safety outcomes.…”
Section: Study Selection Data Extraction and Risk Of Bias Assessmentmentioning
confidence: 99%
“…Rilpivirine (RPV; TMC278; Edurant®) is a secondgeneration non-nucleoside reverse-transcriptase inhibitor (NNRTI) with activity against many viral strains resistant to previous NNRTIs and a moderatehigh genetic barrier to resistance development [1,2]. RPV efficacy and safety have been assessed in registrative randomized controlled clinical trials (RCTs) in HIV-positive treatment-naïve [3][4][5][6][7] and treatmentexperienced patients [8][9][10][11][12][13][14] with documented longterm efficacy and tolerability. Real-life data from observational studies [15][16][17][18][19][20][21] eventually confirmed these results.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2,3 Others clinical trials have shown that the rilpivirine/emtricitabine/TDF combination can maintain virological suppression in antiretroviral (ARV)-experienced virologically-controlled PLHIV. [4][5][6][7][8] In recent trials, the dual therapy dolutegravir/rilpivirine was non-inferior to a current triple antiretroviral therapy (ART) regimen in ARV-experienced virologically-controlled PLHIV at week 48 and efficacy and safety were maintained at week 100. 9,10 It is important to obtain data from real-life settings to assess how rilpivirine is used in routine care and evaluate its virological efficacy, as a complement to data from clinical trials.…”
Section: Introductionmentioning
confidence: 99%